Bovine wellfare handled in adapted corral with unconventional materials - Sartori, Diogo de L. [UNESP]; Nakanishi, Erika Y.; Cravo, Julio C.M.; Martello, Luciane S.; Fiorelli, Juliano (FapUNIFESP (SciELO), 2019)
This study aimed at evaluating bovine behavioral parameters managed in crowding pens built with modular panel of reforestation wood and homogeneous particle sheets of sugarcane bagasse and in conventional wooden crowding pens. The animals treated had their body surface temperature measured by the infrared thermography method and the behavior evaluated through the flight time parameters and the behavior score in the crowding pens. The results indicated that the animals managed in these buildings showed no difference in the behavioral parameters, but the mean and maximum superficial body temperatures were lower in the animals managed in the crowding pens of modular panel.
Keywords: Animal reactivity; Body surface temperature; Particle sheet; Rural buildings